FT-IR and GC-MS characterization of bioactive compounds from the root extract of Anacyclus pyrethrum Linn - Anand, Dr. S. P.; Nagalakshmi, R.; Karthick, S.; Vanathi, S. (International Journal of Environment, Agriculture and Biotechnology, 2024)
Medicinal plants have long been considered for their ability to treat various human diseases owing to their potent phytochemical properties. However, isolating lead compounds from complex mixtures requires extensive knowledge, specialized equipment, and expertise. The emergence of novel diseases underscores the importance of accurately documenting the research on medicinal plants. This study focused on Anacyclus pyrethrum (L.) Lag, an ingredient in Kabasurakudineer. Although traditional and experimental evidence supports various claims regarding these plants, thorough evaluation and utilization of their potential are still necessary. Further research is required to elucidate the mode of action of these isolates. The primary objective of this study was to identify the bioactive compounds in the ethanolic root extract of Anacyclus pyrethrum using Fourier Transform-Infrared (FTIR) and Gas Chromatography-Mass Spectroscopy (GC-MS). FTIR analysis revealed the presence of hydroxyl groups, alcohols, carboxylic acids, aromatic compounds, nitro compounds, alkyl halides, and aryl halides with major peaks at 3740.03, 3281.04, 2903.30, 1612.69, 1402.96, 1242.33, 1023.12, 658.19, and 582.88, respectively, indicating phenols, flavonoids, tannins, and saponins. GC-MS analysis identified 60 compounds, with the major constituents being 4-Decadienamide, N-Isobutyl-, (E, E)-, and (2e,4e)-N-Isobutyldodeca-2,4-Dienamide, constituting 23.03% and 17.33% of the extract, respectively. This study confirmed that the roots of Anacyclus pyrethrum (L.) contain significant natural chemical compounds, validating its traditional use in various pharmacological activities.